Экономические мысли. Политика - Жириновский Владимир Вольфович (1996)
Экземпляры: КХ (19970415) / Инвентарный номер: 1025614 / Цена: 500.00 / Сис.шифр: 66.69 / Авт.знак: Ж 73 / ГРНТИ: 11 / ББК: 66.69(2Рос)